2022
DOI: 10.14202/vetworld.2022.1896-1905
|View full text |Cite
|
Sign up to set email alerts
|

Potency of bacterial sialidase Clostridium perfringens as antiviral of Newcastle disease infections using embryonated chicken egg in ovo model

Abstract: Background and Aim: Clostridium toxins are widely used as medicinal agents. Many active metabolic enzymes, including sialidase (neuraminidase), hyaluronidase, and collagenase, contribute to the mechanism of action of these toxins. Sialidase from Clostridium perfringens recognizes and degrades sialic acid receptors in the host cell glycoprotein, glycolipid, and polysaccharide complexes. Sialic acid promotes the adhesion of various pathogens, including viruses, under pathological conditions. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In previous studies (evaluation and potency) sialidase was known to have the potential to inhibit viral infection both in ovo and in vitro, this was supported by a decrease in the ability of viral replication in exposed host cells. 11,13,24 This study assure and encourage this discovery as shown by the ability of sialidase which has the lowest Gibbs energy value (ΔG) − 7.35 with a Ki value of 4.11 µM towards sialic acid α (2.3)-Gal receptors. This demonstrates its capacity to outcompete viral molecule competitors and attach to sialic acid receptors.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In previous studies (evaluation and potency) sialidase was known to have the potential to inhibit viral infection both in ovo and in vitro, this was supported by a decrease in the ability of viral replication in exposed host cells. 11,13,24 This study assure and encourage this discovery as shown by the ability of sialidase which has the lowest Gibbs energy value (ΔG) − 7.35 with a Ki value of 4.11 µM towards sialic acid α (2.3)-Gal receptors. This demonstrates its capacity to outcompete viral molecule competitors and attach to sialic acid receptors.…”
Section: Discussionsupporting
confidence: 53%
“…Puri ed sialidase enzyme activity was observed using the Neuraminidase assay kit MAK121 (Sigma-Aldrich) with appropriate protocol procedures to obtain a quantitative value in U/ml. 13,14 Chicken Embryo Fibroblast Cell Culture Treatment By Sialidase CEF monolayer cultured cells were obtained from SPF embryonated chicken eggs (ValoBioMedia GmbH, German) age of 8-10 days. Embryo was taken and rinsed brie y with Phosphate Buffered Saline (PBS).…”
Section: Molecular Docking and Interaction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between sialidase NanI and NanJ with sialic acid receptors has been successfully illustrated, predicted, and analyzed in this study using in-silico analysis of a 3D model of the sialidase enzyme from C. perfringens obtained from the PDB data bank. The potency and evaluation of sialidase were known to have the ability to inhibit viral infection both in ovo and in vitro ; this was supported by a decrease in the ability of viral replication in exposed host cells [11– 13] . This study assured and encouraged this discovery, as shown by the ability of sialidase, which has the lowest Gibbs energy value (ΔG) –7.35 with a Ki value of 4.11 µM, towards sialic acid α(2.3)-Gal receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the dialyzed residue was purified by ion exchange using Q Sepharose ® Fast Flow (Merck, Germany), and final purification was performed using affinity chromatography with oxamic acid agarose before being kept at −20°C. Purified sialidase enzyme activity was observed using the Neuraminidase assay kit MAK121 (Sigma-Aldrich) with appropriate protocol procedures to obtain a quantitative value in U/ml [13 , 14] .…”
Section: Methodsmentioning
confidence: 99%